Beat‐to‐beat detection of aortic valve opening in HeartWare left ventricular assist device patients. Issue 5 (9th December 2018) - Clifford, Rachel; Robson, Desiree; Gross, Christoph; Moscato, Francesco; Schima, Heinrich; Jansz, Paul; Macdonald, Peter S.; Hayward, Christopher S.
Abstract: Continuous flow left ventricular assist devices (cfLVADS) result in a significant reduction in aortic valve (AV) opening, which has been associated with several complications. Reliable monitoring of AV opening is needed to determine whether pump speed adjustment may be able to minimize adverse outcomes. We assessed AV status continuously by echocardiography for 4 minutes in 3 states in 18 HeartWare HVAD patients: 2 minutes at rest, and 1 minute each following Valsalva maneuver and supine leg‐raising. Using a previously described algorithm, beat‐to‐beat AV status was compared with the area under the curve of the normalized power spectral density analysis (PSD‐AUC) for the corresponding beats of the pump speed waveform. Five thousand five hundred twenty‐seven beats were analyzed. AV opening varied between 0% and 100% for the cohort with the median AV opening frequency 21.5%, and median duration of opening of 124 msec (range 0–279). The receiver operating characteristic (ROC) curve area for AV opening by the PSD‐AUC algorithm was 0.95 ( P < 0.0001). A PSD‐AUC cut‐off of 0.82 distinguished between an open and closed AV with 86% sensitivity and 93% specificity. Accuracy was similar in regular cardiac rhythm, atrial fibrillation or with frequent ventricular ectopic beats. Valsalva maneuver and leg‐raising had no impact on accuracy. The PSD‐AUC was strongly predictive of AV opening duration ( P < 0.0001). We found that AV status and opening duration can be determined with high accuracy on a beat‐to‐beat basis irrespective of cardiac rhythm and with low level exercise and changes in filling.